Practical guide to organization design - Davis, Margaret R. (Crisp Pub. Menlo ParkUS, 1996)
Defines organization design and provides guidelines for designing/re-designing a business organization. Includes topics such as: business processes, organization structure, workflow charting, management structure, and coordination and control of group and individual activities. Provides guidelines for developing instruments for measuring performance; and for implementing changes in organization design.